PENGEMBANGAN GERAK SENAM AEROBIK BERBASIS TARIAN TRADISIONAL - Poerwanto, Ari; Haetami, Mimi; Gustian, Uray (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe more rapid globalization increasingly eroded the local culture in the archipelago, so as to weaken the existence of regional dances, the purpose of this study is to bring up new gymnastic motion models taken from traditional dance movements including the Zapin Melayu and Kanjan Dayak Kebahant dance movements. consists of two stages: the pre-development stage and the development stage. The pre-development stage consists of a literature review, a study of relevant research and a field study. The development stage consists of the preparation of aerobic exercise based on traditional dance, expert validation, small and large scale trials. Validation involves 3 experts, small-scale trials involving 5 people and large-scale trials involving 20 people. The instrument used is. Interviews, field notes and questionnaires. The results in the form of aerobic exercise models based on traditional dances consisting of 11 sets of heating movements, 10 core movements and 8 cooling movements assessment 3 traditional dance-based aerobics experts have fulfilled full of music, gymnastics, and dance . Based on the results of small and large scale trials aimed at participants of traditional dance based aerobics can be accepted as very good, thus concluded that aerobic exercise based on traditional dances can be accepted in the community.Keywords: Exercise Gymnastics, Aerobic Based, Traditional Dances